Mechanoregulation of angiopoietin-like 4 in epithelial-mesenchymal transition and cancer metastasis - Liao, Zehuan (Nanyang Technological University, 2024)
The epithelial-mesenchymal transition (EMT) serves as a pivotal mechanism in the progression of metastatic cancer. However, current research, predominantly reliant on 2D monolayer cultures, inadequately replicates the intricate nature of a 3D tumor microenvironment. In the main project (Paper I), we investigated the transcriptomes of various cancer cell types undergoing EMT in both 2D and 3D cultures with different EMT inducers. We identified a 3D EMT gene signature that has broad implications across different types of human cancers. Angiopoietin-like 4 protein (ANGPTL4) was found to be a top ranked hub gene with clinical relevance and impact. Our study also revealed the mechanoregulation of ANGPTL4, which corroborated with its high expression in advanced tumors. Consistently, ANGPTL4 deficiency attenuated primary tumor growth and EMT of cancer cells. These findings suggest that targeting ANGPTL4 may be a promising approach to inhibit EMT and prevent cancer progression. In the collaborative project (Paper II), we studied the regulation of membrane microenvironment and signal transduction in natural killer (NK) cells, a group of innate immune cells involved in the tumor microenvironment (TME) and cancer immunotherapy. Here, we revealed the PIP2-regulated recruitment of DAP12 homodimer to lipid raft boundary of NK cells. In another collaborative project (Paper III), we introduce HTCA, a single-cell RNA-sequencing database with various user-friendly analysis tools. Collectively, our main findings reflect the intricate regulation of physical stiffness within the TME influencing EMT signaling in cancer cells, where ANGPTL4 emerges as a crucial player. Our comprehensive analyses strongly underscore the clinical significance of ANGPTL4, particularly in advanced stage cancer, aligning with our broader understanding of tumors in patients. In essence, our study vividly demonstrates how the TME's stiffness orchestrates the mechanoregulation of ANGPTL4, a hub gene within the 3D EMT gene signature.